2020
DOI: 10.1080/15592294.2020.1747777
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inclusion of plant ingredients induces epigenetic changes in the intestine of zebrafish

Abstract: Epigenetic modifications, such as DNA methylation, can be regulated by nutrition and dietary factors. There has been a large increase in the use of sustainable plant-based protein sources in fish feed due to limitations of fishmeal resources, which are needed to sustain a rapidly growing aquaculture industry. With this major transition from marine ingredients to plant-based diets, fish are abruptly introduced to changes in dietary composition and exposed to a variety of phytochemicals, some of which known to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Age-related diseases, including cancer, result from one or more failures at cellular and molecular levels, making difficult the identification of molecular targets for their prevention and treatment. Cancer prevention is an important theme for healthy aging and the role of the quality of one's diet for cancer prevention is definitely worthy of attention [34][35][36][37][38]. As for oral cancer, regarded as the main cause of death from oral diseases in many countries with the global estimates in 2018 of 354,864 new cases and 177,384 deaths, chemoprevention by dietary agents has evolved as a promising approach to control the incidence which has increased in many countries, especially in younger age groups [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-related diseases, including cancer, result from one or more failures at cellular and molecular levels, making difficult the identification of molecular targets for their prevention and treatment. Cancer prevention is an important theme for healthy aging and the role of the quality of one's diet for cancer prevention is definitely worthy of attention [34][35][36][37][38]. As for oral cancer, regarded as the main cause of death from oral diseases in many countries with the global estimates in 2018 of 354,864 new cases and 177,384 deaths, chemoprevention by dietary agents has evolved as a promising approach to control the incidence which has increased in many countries, especially in younger age groups [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…As for oral cancer, regarded as the main cause of death from oral diseases in many countries with the global estimates in 2018 of 354,864 new cases and 177,384 deaths, chemoprevention by dietary agents has evolved as a promising approach to control the incidence which has increased in many countries, especially in younger age groups [39,40]. The application of antioxidants or functional foods containing nutrients able to reverse or change epigenetic phenomena, makes nutrition a natural weapon to prevent cancer and improve health span [34][35][36][37][38]. In vitro evaluation of the anticancer effects of lactoferrin and tea polyphenol combination on Cal 27 cells showed a synergistic inhibition with induction of apoptosis and mitochondrial permeability transition [40].…”
Section: Discussionmentioning
confidence: 99%
“…The potential of the WG-based diet to trigger sensitivity responses in salmon is also supported by a previous experiment conducted in zebrafish using the same feed ingredients as in this study. Increased infiltration of eosinophilic granulocytes to the intestinal lumen was revealed by histology of the mid-intestine of gluten-fed zebrafish [ 47 ]. In humans, gluten sensitivity or celiac disease has been shown to be connected to neurological dysfunctions in addition to intestinal and extra-intestinal symptoms [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, gluten sensitivity or celiac disease has been shown to be connected to neurological dysfunctions in addition to intestinal and extra-intestinal symptoms [ 48 ]. Similarly, the WG30-fed salmon showed a differential expression of several neural genes expressed in the mid-intestine, which can affect enteric nervous system-controlled gut functions like satiety or hunger [ 47 , 49 ]. Further studies are needed to understand the consequences of WG-based fish diets on neural functions and gut-to-brain signal transmission in fish and the impact on fish welfare.…”
Section: Discussionmentioning
confidence: 99%
“…Even though those gene expression changes have not significantly influenced their growth, we believe that these molecular adjustments occurred in the muscle to maintain muscle homeostasis following imbalances caused by dietary plant ingredients. Moreover, our recently published study (Dhanasiri et al, 2020) from the same feeding trial also indicated plantbased diets induced epigenetic changes in the intestine with mild inflammation without significantly affecting their growth.…”
Section: Discussionmentioning
confidence: 72%